2022
DOI: 10.3390/diagnostics12071707
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Objective Structured Clinical Examination on Diagnostic Musculoskeletal Ultrasonography Training in Undergraduate Traditional Korean Medicine Education: An Action Research

Abstract: This study aimed to report the specific methods and investigate the educational effects of diagnostic musculoskeletal ultrasound training and the Objective Structured Clinical Examination (OSCE) for traditional medicine students. Scanning volar wrist and diagnosing carpal tunnel syndrome were selected for musculoskeletal ultrasound to train students to use the basic functions of the ultrasound device and scan various structures including tendons, nerves, and arteries. The students were divided into two groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
0
5
0
1
Order By: Relevance
“…최근 침 시술에서 초음파를 사용하여 안전하고 효과적인 침 시술을 도모하는 사례가 증가하고 있다 15) . 초음파 유도하 침 시술은 환자에 따른 변이 측정에 용이하며, 특히 비숙련자에 있어서 정확한 시술을 돕는다는 연구 또한 존재한다 16,17) . 초음…”
Section: Discussion and Conclusion Discussion And Conclusionunclassified
“…최근 침 시술에서 초음파를 사용하여 안전하고 효과적인 침 시술을 도모하는 사례가 증가하고 있다 15) . 초음파 유도하 침 시술은 환자에 따른 변이 측정에 용이하며, 특히 비숙련자에 있어서 정확한 시술을 돕는다는 연구 또한 존재한다 16,17) . 초음…”
Section: Discussion and Conclusion Discussion And Conclusionunclassified
“…Recent studies have suggested that using ultrasonography may be helpful for avoiding adverse event following acupuncture treatments and educational efficacy [ 19 , 20 , 21 , 22 , 23 ]. In the results of this study, it was also possible to predict the tendency of the ANIR to appear deeper when the BMI of subjects increased, but it was difficult to know whether the liver was damaged when the acupuncture needle was actually inserted.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography may also be beneficial in minimizing side events during acupuncture treatments as well as educational benefits of correct needle positioning [14][15][16][17]. This study is significant in that it is the first study to analyze the needling depth and anatomical characteristics of acupoint CV23 using ultrasound.…”
Section: Menmentioning
confidence: 98%